OPEN GOVERNMENT PATNERSHIP (OGP) UPAYA MENINGKATKAN KUALITAS LAYANAN MASYARAKAT DESA PEJAMBON - Arifin, Zainul; Priyo Sigit Akbar Pambudi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
Pejambon Village is one of the villages with an area of 189,190 hectares with a population of around 2126 people. Since the end of 2016, this village has implemented the Open Government Partnership (OGP). The purpose of this study is to describe and analyze community participation in the implementation of the open government partnership of the Pejambon Village Government and its influence on the improvement of welfare and the quality of services they receive. The research method used is qualitative descriptive. The result is the Open Government Partnership which is implemented in Pejambon village by involving stakeholder participation in the process starting from development planning, implementation, evaluation to the utilization of development results, although not perfect, but has been able to answer problems related to transparency, ease of access to public service information, and government policies which are currently considered to be lacking, and have even become one of the solutions to improve welfare community towards village development. This happens because in its implementation, the Open Government Partnership in Pejambon Village is carried out by providing the widest possible opportunities and opportunities for all stakeholders, ranging from the community, PPID, Bojonegoro Institute and the Communication and Informatics Office to direct their resources and potentials starting from the planning, decision-making and evaluation processes of development activities carried out.